The Interplay of Phototrophic and Heterotrophic Microbes Under Oil Exposure: A Microcosm Study - Kamalanathan, Manoj; Schwehr, Kathleen A.; Labonté, Jessica M.; Taylor, Christian; Bergen, Charles; Patterson, Nicole; Claflin, Noah; Santschi, Peter H.; Quigg, Antonietta (Frontiers in Microbiology, 2021)
Microbial interactions influence nearly one-half of the global biogeochemical flux of major elements of the marine ecosystem. Despite their ecological importance, microbial interactions remain poorly understood and even less is known regarding the effects of anthropogenic perturbations on these microbial interactions. The Deepwater Horizon oil-spill exposed the Gulf of Mexico to 4.9 million barrels of crude oil over 87 days. We determined the effects of oil exposure on microbial interactions using short and long-term microcosm experiments with and without Macondo surrogate oil. Microbial activity determined using radiotracers revealed that oil exposure negatively affected substrate uptake by prokaryotes within 8 h, and by eukaryotes over 72 h. Eukaryotic uptake of heterotrophic exopolymeric substances (EPS) was more severely affected than prokaryotic uptake of phototrophic EPS. In addition, our long-term exposure study showed severe effects on photosynthetic activity. Lastly, changes in microbial relative abundances and fewer co-occurrences amongst microbial species were mostly driven by photosynthetic activity, treatment (control vs oil), and prokaryotic heterotrophic metabolism. Overall, oil exposure affected microbial co-occurrence and/or interactions possibly by either direct reduction in abundance of one of the interacting community members.